Handling complaints at bin baz son islamic boarding school - Widiyanto; Ahmad Mulalic (At Turots: Jurnal Pendidikan Islam, 2024)
The purpose of this study is to identify the different types of complaints, the components that cause complaints, and the methods used to handle complaints. The Bin Baz Son Islamic Center Islamic Boarding School in Yogyakarta is the place where this investigation was carried out. Qualitative descriptive methods are used to collect data through observation, documentation, and interviews. The results of the study showed that there were nine types of complaints that emerged related to problems: cleanliness, safety, food quality, health, complaint services, intracurricular activities, additional needs, facilities and infrastructure, and laundry. The responsibility of the mudir, the head of the pesantren division, the head of caregiving, and the caregiver to handle complaints. Management functions such as planning, organizing, mobilizing, and supervising are used in the management of complaints that arise. This study found that, even though there was no Standard Operating Procedure (SOP) officially issued by the head of the boarding school, the handling of complaints from the guardians of students and students at the Bin Baz Putra Center of the Islamic Boarding School went well. This is shown by the lack of guardians of students who attract their children to be transferred to other Islamic boarding schools and the number of students who continue to increase every year.